PRE-SERVICE EFL TEACHERS’ SELF-EFFICACY, THEIR ENGLISH PROFICIENCY AND THEIR PREPAREDNESS FOR TEACHING PRACTICUM PROGRAM - Nugroho, Himmawan Adi (UNIVERSITAS MUHAMMADIYAH METRO ( MUHAMMADIYAH UNIVERSITY OF METRO), 2017)
Teacher training institutions hold an important role in preparing their students, the prospective or pre-service teachers, to become professional teachers based on their specific fields of study. This study examined the pre-service EFL teachers’ perception of self-efficacy and their English proficiency toward their preparedness for the teaching practicum program. The study used a survey research design using questionnaire as the instrument to get the pre-service EFL teachers’ perception of self-efficacy. The English proficiency data was from the TEP (test of English proficiency) collected from the university’s language center where the pre-service EFL teachers took the test. Findings show that the pre-service EFL teachers have medium to high self-efficacy toward their teaching of EFL. They feel ready in spite of the fact they still have the feeling of anxiety. The courses related with the preparation to become a good and qualified EFL teachers and also for the teaching practicum program helped them to feel more confident.